Moral Message of Lifebuoy Shampoo Advertisement Strong Roots Edition in the Holy Month (Roland Barthes Semiotic Analysis (Proceeding of Dakwah Saizu International Conference, 2023)
Ramadan is the holy month of Muslims around the world. This month, all Muslims are required to fast for a full month. This month, many positive activities and advertisements contain moral messages. Messages that are packaged and conveyed attractively are an effective way to increase the attractiveness of the person receiving the message. Like conveying a moral message through advertising, in addition to the moral message being conveyed, it also attracts consumers towards the advertised product. This study aims to analyze and describe the moral message in the advertisement for Lifeboy shampoo, which was specially presented in the month of Ramadan with the title "Akar Kuat di Bulan Suci" through its YouTube account, Lifebouy ID. The object of this research is the Lifebouy shampoo advertisement "Strong Roots in the Holy Month" edition. This type of research is a content analysis using a qualitative approach by analyzing and describing phenomena, social activities, events, attitudes, perceptions, beliefs, and individual and group thoughts; then, the final result is in written words. The theory used in this study is Roland Barthes' semiotic theory, which is divided into two types: communication semiotics and significant semiotics. Communication semiotics emphasizes the theory of sign production, while significant semiotics emphasizes signs and their understanding in certain contexts. Roland Barthes' theory develops semiotics into two levels, namely denotation and connotation. Based on the analysis using Roland Barthes' semiotic theory in the advertisement "Akar Kuat di Bulan Suci," the researcher found several moral messages contained in the advertisement: politeness, character, ethics, and manners; this is done and becomes a role model in life.